Работы по мониторингу курганов степной части Украины - Дараган, М.Н.; Полин, С.В.; Разумов, С.Н. (Археологічні дослідження в Україні, 2010)
Within the program of monitoring of barrows in the steppe region of Ukraine a tacheometric survey of Chekereska Mohyla group was made. Advantages of implementation of tacheometric survey in archaeological prospecting is shown as an effective instrument in determination, with help of fixing the smallest swings of heights, of the existence of barrows with features hardly seen in relief and of their form and dimensions.